2021
DOI: 10.1155/2021/5558066
|View full text |Cite
|
Sign up to set email alerts
|

The Combination Treatment of Curcumin and Probucol Protects Chondrocytes from TNF‐α Induced Inflammation by Enhancing Autophagy and Reducing Apoptosis via the PI3K‐Akt‐mTOR Pathway

Abstract: Osteoarthritis (OA) is a chronic joint disease characterized by cholesterol accumulation in chondrocytes, cartilage degeneration, as well as extracellular matrix (ECM) destruction, and joint dysfunction. Curcumin, a chemical that can reduce cholesterol levels in OA patients, also can inhibit the progression of OA. However, a high concentration of curcumin may also trigger apoptosis in normal chondrocytes. Besides curcumin, probucol that is found can also effectively decrease the cholesterol level in OA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The PI3K/AKT/mTOR signalling pathway is closely related to chondrocyte apoptosis and autophagy 30 . Therefore, PI3K/AKT/mTOR signalling pathway was investigated to further understand the mechanisms through which OI decreases apoptosis and promotes autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signalling pathway is closely related to chondrocyte apoptosis and autophagy 30 . Therefore, PI3K/AKT/mTOR signalling pathway was investigated to further understand the mechanisms through which OI decreases apoptosis and promotes autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…The regulatory mechanisms of autophagy are very complex. The PI3K/AKT/mTOR pathway, an essential intracellular signaling pathway, is closely related to chondrocyte apoptosis and autophagy [ 37 ]. Moreover, activation of the PI3K/Akt/mTOR signaling pathway is also critical in the occurrence and development of OA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that activating PI3K can reduce MMP-13 expression. 52 However, other investigations have shown that specific PI3K and AKT inhibitors can drastically lower MMP expression. 53 These findings highlight the fact that the PI3K/AKT pathway functions as a double-edged sword in ECM metabolism.…”
Section: Discussionmentioning
confidence: 98%